Impact Evaluation of School Feeding Programme in Osun State Primary Schools (2014)
Poor nutrition contribute to low academic performance, high dropout rates, decrease in enrolment and irregular attendance in schools. A school feeding programme was started in Osun state in 2005. To date, there is little or no empirical evidence on the impact of the programme. This study, therefore, investigated the impact of the feeding programme oneducational indicators and social skills of the beneficiaries. The study adopted a non-equivalent, control group post-test only design. Multi-stage sampling was used to select 450 pupils each from primary two (who have participated in the feeding programme for four years) in Osun State, and 450 pupils from primary two in Oyo State which served as the control. Four hundred and fifty parents of the pupils from Osun state, 45 intact classes of primary four, 45 head teachers, 109 stakeholders (teachers, teachers‘ supervisor, Local Government Education Authority Secretaries, School feeding Agency staff) and 60 cooks involved in the programme were also selected. Seven instruments were administered, namely: School Resources Inventory (r=0.82) (to the head-teachers), Parents Perception of School Feeding Programme (r=0.77) (to the parent of the pupils), School Feeding Programme Operators Questionnaire (r=0.74) (to the stakeholders), Cook Empowerment Questionnaire (r=0.82) (to the cooks), Achievement Test in Numeracy (r=0.84) (to pupils), Achievement Test in Literacy (r=0.78) (to pupils) and Standard Balance Beam Scale physically used to measure pupils‘ weight and height. Data collection took place from October to December 2012. Data were analysed using descriptive and inferential statistics at p<0.05. Average enrolment in primary two increased by 19.2%, attendance rate was raised by 9.2% and retention rates increased by 3% after feeding started. Intervention schools showed significant increases in enrolment (t(43) =2.41) and attendance (t(43) =2.909). Boys‘ and girls‘ enrolment, were not different in the intervention schools, but boys‘ enrolment was significantly higher (t (28) =2.08) in non-intervention schools. Girls‘ attendance were significantly higher (t (58) = -2.23) in intervention schools, while that of boys‘ were higher (t (28) =2.15) in non-intervention schools. There was higher nutrition status (t(898)=4.62) for pupils‘ in intervention schools. In respect to achievement, intervention schools were significantly higher in numeracy (t(898) =5.43) and literacy (t(898) = 9.69) girls‘ in intervention schools were significantly higher in numeracy (t(448) = -5.36) and literacy (t (448)=-3.86) also, girls‘ in non-intervention schools were significantly higher in numeracy (t(448) = -2.01) but no difference in boys‘ and girls‘ literacy achievement. Girls‘ nutrition status was higher (t (448) = -2.62) than boys‘ in the intervention schools. Parents (363/80.6%) and stakeholders (99/90.9%) indicated satisfaction with implementation of the programme. Cooks‘ income showed significant increase (t (59) =15.7) and (50/83.3%) of them perceived that the training received improved their purchasing skills. School feeding programme in Osun state made a positive impact on pupils‘ enrolment, attendance, retention, nutrition status and academic achievement and benefited a wide range of stakeholders. Non-implementing states should be encouraged to replicate the School Feeding Programme and sustain it beyond primary two